2017
DOI: 10.1007/s10439-017-1820-x
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Gait Features in Older Adults Walking on Inclined Surfaces at Different Speeds

Abstract: This study evaluated linear and nonlinear gait features in healthy older adults walking on inclined surfaces at different speeds. Thirty-seven active older adults (experimental group) and fifty young adults (control group) walked on a treadmill at 100% and ±20% of their preferred walking speed for 4 min under horizontal (0%), upward (UP) (+8%), and downward (DOWN) (-8%) conditions. Linear gait variability was assessed using the average standard deviation of trunk acceleration between strides (VAR). Gait stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Eighteen studies considered research questions focused on the faller-non-faller (F-NF) comparison [27][28][29][30][31][32][33][34][35][36][37][38][39]. Fifteen studies investigated the young-old (YO) comparison [3,6,7,9,38,[40][41][42][43][44][45][46][47][48][49]. Six studies conducted F-NF and YO comparisons [33,[50][51][52][53][54].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies considered research questions focused on the faller-non-faller (F-NF) comparison [27][28][29][30][31][32][33][34][35][36][37][38][39]. Fifteen studies investigated the young-old (YO) comparison [3,6,7,9,38,[40][41][42][43][44][45][46][47][48][49]. Six studies conducted F-NF and YO comparisons [33,[50][51][52][53][54].…”
Section: Resultsmentioning
confidence: 99%
“…Constant-load treadmill test. As spatiotemporal gait parameters are influenced by speed and slope, 31,32 a constant-load treadmill test was performed. 20 The test was usually performed at 3.2 km/h with a 12% slope.…”
Section: Assessmentsmentioning
confidence: 99%
“…The MLE is based on the Lyapunov's theory of dynamic stability, initially formulated to assess the sensitivity of a mechanical system to small perturbations and is often used to quantify how the patterns of gait kinematics change in response to small perturbations 7,11 . While arguments can be made for any of the deriving stability measures, recent reviews suggested the use of the MLE as a prominent measure of dynamic stability 32,38,39 and has thus received extensive focus in the recent years [138][139][140][141][142][143]39,144,145 .…”
Section: Introductionmentioning
confidence: 99%